The Role of Gender in the Preconscious Processing of Facial Trustworthiness and Dominance - Wang, Haiyang; Tong, Shuo; Shang, Junchen; Chen, Wenfeng (Frontiers in Psychology, 2019)
The present study adopted the breaking continuous flash suppression paradigm (b-CFS) to investigate how Chinese participants process trustworthiness (Experiment 1) and dominance (Experiment 2) at the preconscious level. In addition, we tested whether the gender of a face and the gender of a participant can influence the preconscious processing of facial trustworthiness and dominance. Experiment 1 showed that the least and most trustworthy faces both took significantly less time to break into awareness than neutral faces. In Experiment 2, for female faces, neutral faces took significantly less time to break into awareness than the least and most dominant faces. In both experiments, female faces broke through suppression faster than male faces. In summary, for Chinese participants, the preconscious processing of trustworthiness was not different between male and female faces. However, the preconscious processing of dominance was different between male and female faces.